2008
DOI: 10.2147/vhrm.s2605
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in the elderly: a review on clinical, instrumental and laboratory presentation

Abstract: Objective: Diagnosis of pulmonary embolism (PE) remains diffi cult and is often missed in the elderly due to nonspecifi c and atypical presentation. Diagnostic algorithms able to rule out PE and validated in young adult patients may have reduced applicability in elderly patients, which increases the number of diagnostic tools use and costs. The aim of the present study was to analyze the reported clinical presentation of PE in patients aged 65 and more. Materials and Methods: Prospective and retrospective Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
4
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
2
19
4
7
Order By: Relevance
“…Moreover, the studies are subject to underrecognition of VTE as symptoms may be nonspecific and masked by comorbidity in older patients. [30][31][32][33][34] Also VTE is often silent, [35][36][37] and a previous study found prevalence of 13.5% DVT by ultrasonography screening of institutionalised older individuals.…”
Section: Discuss This Articlementioning
confidence: 94%
“…Moreover, the studies are subject to underrecognition of VTE as symptoms may be nonspecific and masked by comorbidity in older patients. [30][31][32][33][34] Also VTE is often silent, [35][36][37] and a previous study found prevalence of 13.5% DVT by ultrasonography screening of institutionalised older individuals.…”
Section: Discuss This Articlementioning
confidence: 94%
“…The study by Sellier et al (2008) identified the presence of isolated distal DVTs compared with proximal DVTs in the older patients in post-acute care facilities, respectively 10% versus 4% of those diagnosed with DVTs. PE is underdiagnosed in older patients, while its incidence and risk increases steadily with age, because older patients have nonspecific and atypical presentation of PE (Masotti et al, 2008). This study showed that PE diagnoses were lower in the older inpatients than the younger inpatients.…”
Section: Vte Incidence In the Older Adult Populationmentioning
confidence: 59%
“…Diagnosis of acute PE remains a challenge due to non-specific presentation in terms of signs, instrumental and laboratory findings, especially in the older patients such as those of our study. 28 Physicians should increase their efforts to reduce misdiagnoses and diagnostic delays. Clinical suspicion should be the primum movens for diagnosis of acute PE and the estimation of pre-test probability (PTP) by using validated tools, such as Wells or Geneva scores, may rise it.…”
Section: Discussionmentioning
confidence: 99%
“…Immobility remains one of the most frequent risk factors for VTE, especially in elderly patients and our study confirms it in agreement with literature. [9][10][11][12][13][14]17,28 In TUSCAN-PE around one third of patients discharged with PE from Internal Medicine wards has active cancer. This finding is higher compared to the most [ Management of acute pulmonary embolism recent studies, such as IPER, EMPEROR, MASTER, SWIVTER and ZATPOL, but similar to that observed in the Italian population of RIETE registry.…”
Section: Discussionmentioning
confidence: 99%